Effectiveness of Game Health Education Anemia (GHEA) Guided by the Health Belief Model on Improving Knowledge and Attitudes Toward Iron-Deficiency Anemia Prevention Among Adolescent Girls: A Quasi-Experimental Study - Fauzi, Imam Nur; Kumboyono, Kumboyono; Fevriasanty, Fransiska Imavike (Journal of Applied Nursing and Health, 2025)
Background: Iron-deficiency anemia (IDA) remains a significant health problem among adolescent girls, affecting growth, academic achievement, and reproductive health. Traditional education methods like lectures and booklets are often less engaging and ineffective in changing behavior. Few studies have tested gamified, theory-based health education for anemia prevention in Indonesian adolescents. This study evaluated the effectiveness of the Game Health Education Anemia (GHEA) compared with a Digital Pocket Book in improving knowledge and attitudes toward IDA prevention among adolescent girls. Methods: A quasi-experimental study, guided by the Health Belief Model (HBM) and reported according to the TREND checklist, was conducted at SMP Islam Ma’arif 02 Malang, Indonesia, in June 2025. Sixty female adolescents were selected through purposive sampling based on power analysis (effect size = 1.12, α = 0.05, power = 0.95). Inclusion criteria were female students aged 12–18 years, healthy, and owning a digital device; exclusion criteria were prior exposure to digital anemia education or incomplete participation. Participants were equally assigned to an intervention group (GHEA) and a control group (the Digital Pocket Book). Data were collected using a validated questionnaire and analyzed with Wilcoxon signed-rank, paired t-, and Mann–Whitney U tests at a 0.05 significance level. Results: The mean age of participants was 14 years (range 13–15). The GHEA group showed significant improvements in knowledge (Z = -4.847, p < 0.001) and attitudes (Z = -4.275, p < 0.001), while the control group showed smaller yet significant gains. Between-group analysis revealed higher post-test scores in the intervention group for both knowledge (Z = -5.284, p < 0.001) and attitudes (Z = -3.081, p = 0.002). Conclusion: The GHEA intervention was more effective than the Digital Pocket Book in improving adolescents’ knowledge and attitudes toward IDA prevention, indicating that gamification-based education can serve as an engaging and effective tool for school-based health promotion